Immunotherapy in endometrial cancer: rationale, practice and perspectives - Wenyu Cao; Xinyue Ma; Jean Victoria Fischer; Chenggong Sun; Beihua Kong; Qing Zhang (BMC, 2021)
Abstract Tumor immunotherapy has attracted more and more attention nowadays, and multiple clinical trials have confirmed its effect in a variety of solid tumors. Immune checkpoint inhibitors (ICIs), cancer vaccines, adoptive cell transfer (ACT), and lymphocyte-promoting cytokines are the main immunotherapy methods. Endometrial cancer (EC) is one of the most frequent tumors in women and the prognosis of recurrent or metastatic EC is poor. Since molecular classification has been applied to EC, immunotherapy for different EC subtypes (especially POLE and MSI-H) has gradually attracted attention. In this review, we focus on the expression and molecular basis of the main biomarkers in the immunotherapy of EC firstly, as well as their clinical application significance and limitations. Blocking tumor immune checkpoints is one of the most effective strategies for cancer treatment in recent years, and has now become the focus in the field of tumor research and treatment. We summarized clinical date of planned and ongoing clinical trials and introduced other common immunotherapy methods in EC, such as cancer vaccine and ACT. Hormone aberrations, metabolic syndrome (MetS) and p53 mutant and that affect the immunotherapy of endometrial cancer will also be discussed in this review.